Peran Satuan Polisi Pamong Praja dalam Menertibkan Pedagang Kaki Lima untuk Menjamin Ketertiban Umum di Kabupaten Karawang - Sukmawati, Sukmawati; Akbar, Muhammad Gary Gagarin; Abas, Muhamad (Fakultas Hukum Universitas PGRI Palangkaraya, 2024)
Street vendors are often viewed negatively due to their occupation of sidewalks and disruption of traffic order. This research highlights the crucial role of government intervention in organizing street vendors to ensure public order in Karawang Regency. Despite existing regulations, managing street vendors effectively remains a challenge primarily due to enforcement difficulties and the potential economic displacement of vendors. This study aims to assess the responsibility and effectiveness of the Karawang Municipal Police Unit (Satpol PP) in regulating street vendors without causing significant disruptions to their livelihoods. The research employs an empirical juridical methodology, analyzing relevant laws and their real-world application using field data. The findings indicate that the role of Satpol PP in implementing regulations related to street vendors includes preemptive actions, preventive measures, and repressive actions such as the relocation and demolition of illegal setups as mandated by Regional Regulation No. 10 of 2020 on Public Order, Community Tranquility, and Community Protection. However, challenges persist, including insufficient personnel and resources, the public's limited understanding of regulations, and lack of support from community organizations. This study emphasizes the need to strengthen Satpol PP’s capacity and improve public awareness to ensure the effective regulation of street vendors.